Competencies for Program Evaluators in Light of Adaptive Action: What? So What? Now What?. Issue 145 (March 2015) - King, Jean A.; Stevahn, Laurie
Abstract: This chapter considers next steps in the development and use of evaluator competencies in the United States and globally. It begins with a brief grounding in definitions, then applies the framework of adaptive action (Eoyang & Holladay, 2013), asking "What?" to first describe the current status of evaluator competencies, "So what?" to discuss the implications of that status, and finally "Now what?" to identify potential actions that might attend to the complexity of change in the field of evaluation. © Wiley Periodicals, Inc., and the American Evaluation Association.